Animal Models of Alcoholic Liver Disease: Pathogenesis and Clinical Relevance - Gao, Bin; Xu, Ming-Jiang; Bertola, Adeline; Wang, Hua; Zhou, Zhou; Liangpunsakul, Suthat (Gene expression, 2017)
Alcoholic liver disease (ALD), a leading cause of chronic liver injury worldwide, comprises a range of disorders including simple steatosis, steatohepatitis, cirrhosis, and hepatocellular carcinoma. Over the last five decades, many animal models for the study of ALD pathogenesis have been developed. Recently, a chronic-plus-binge ethanol feeding model was reported. This model induces significant steatosis, hepatic neutrophil infiltration, and liver injury. A clinically relevant model of high-fat diet feeding plus binge ethanol was also developed, which highlights the risk of excessive binge drinking in obese/overweight individuals. All of these models recapitulate some features of the different stages of ALD and have been widely used by many investigators to study the pathogenesis of ALD and to test for therapeutic drugs/components. However, these models are somewhat variable, depending on mouse genetic background, ethanol dose, and animal facility environment. This review focuses on these models and discusses these variations and some methods to improve the feeding protocol. The pathogenesis, clinical relevance, and translational studies of these models are also discussed.